2000
DOI: 10.2214/ajr.174.3.1740699
|View full text |Cite
|
Sign up to set email alerts
|

Perihepatic Lymph Nodes as a Marker of Antiviral Response in Patients with Chronic Hepatitis C Infection

Abstract: Total perihepatic lymph node volume changes according to the antiviral response and leads to progressive normalization of the perihepatic lymph node volume in sustained virologic responders. A decrease in the perihepatic lymph node volume is associated with an improvement in liver histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 13 publications
4
35
0
8
Order By: Relevance
“…no. 8 ln has previously been observed in 77-91% of cHc patients (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and 96% of cHB patients (14). in our study, the no.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…no. 8 ln has previously been observed in 77-91% of cHc patients (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and 96% of cHB patients (14). in our study, the no.…”
Section: Discussionsupporting
confidence: 66%
“…regarding lymph node size, there have been many reports of the relationship between chronic liver diseases and lymph nodes investigated by ultrasonography (8)(9)(10)(11)(12). However, none of the studies used the ln index (major x minor axis of the lymph node) for the side index lymph nodes, established the aST, aspartate aminotransferase; alT, alanine aminotransferase; ALB, albumin; ALP, alkaline phosphatase; γ-GTP,γ-glutamyltranspeptidase; cHe, cholinesterase; PlT, platelets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjects with HCV infection and normal ALT values were followed up, and the results showed that those with increases in ALT levels had lymph nodes larger than those of subjects with persistently normal ALT levels. 25 Nodal sizes were also positively correlated with viremia 19,22 and could be markers for the virological response in the treatment of chronic hepatitis C. 29,32 However, they may be correlated with serological values that would consequently become controversial. 17,22,24,29 Our study demonstrated that different parameters of nodal size led to different results and that nodal width might be superior to other parameters in terms of representing a lymph node in its reactive state.…”
Section: Discussionmentioning
confidence: 99%